Business English teaching: different approaches for different needs - Vian Jr., Orlando (The ESPecialist, 2014)
This text aims at discussing possible approaches to teaching English for Business in professional contexts and in economics, business administration and accounting under graduation courses based on learners’ needs. Based on the Brazilian English for Specific Purposes scenario as well as on the notions of ‘approach’ and ‘need’, six different approaches are presented: task-based, deep end, case study, lexical, genre-based, focus on gambits and focus on business skills. Finally, materials and the applicability of such approaches to the contexts of practice are discussed.